The changing role of teachers in embedding ICTs into the curriculum: a case study in a Tasmanian school - Purnell, Dianne (Curtin University, 2002)
Information Communication Technology (ICT) can provide innovative learning experiences, but in all cases a great deal depends upon the teacher to provide the context to make this possible. This study focuses on the role of teachers and their needs in embedding Information Communication Technologies into the curriculum in a Tasmanian Government Senior Secondary College.The purpose of the study was to explore what support and encouragement teachers need to successfully incorporate ICTs into the curriculum. In particular, it looks at what motivates teachers to change their practice, in what ways their practice changes and what support is essential for that change to be lasting and worthwhile.Three learning areas were selected for the study, LOTE, English, and Mathematics. There were a total of eleven teachers plus the researcher and eight classes of students. The majority of data collected was qualitative in the form of documents, interview and observations. Quantitative data was collected mainly through surveys.The study focused on the following key elements required for teachers to embed ICTs into the curriculum:1) The role of management;2) The role of teachers (pedagogical, technical);3) Requirements for technical assistance;4) Time allocation; and5) Professional development.Resulting from the study are a series of recommendations for education departments, Principals, ICT managers and teachers to assist them in implement the embedding of ICTs into the curriculum.